Perfluorocarbon Emulsion Contrast Agents: A Mini Review - Holman, Ryan; Lorton, Orane; Guillemin, Pauline C.; Desgranges, Stéphane; Contino-Pépin, Christiane; Salomir, Rares (Frontiers in Chemistry, 2022)
Perfluorocarbon emulsions offer a variety of applications in medical imaging. The substances can be useful for most radiological imaging modalities; including, magnetic resonance imaging, ultrasonography, computed tomography, and positron emission tomography. Recently, the substance has gained much interest for theranostics, with both imaging and therapeutic potential. As MRI sequences improve and more widespread access to 19F-MRI coils become available, perfluorocarbon emulsions have great potential for new commercial imaging agents, due to high fluorine content and previous regulatory approval as antihypoxants and blood substitutes. This mini review aims to discuss the chemistry and physics of these contrast agents, in addition to highlighting some of the past, recent, and potential applications.